Entrepreneurial Engagements - Chikelue Chris Akabuike (Artivate, 2023)
This study addresses the experiences of undergraduate entrepreneurs, including what motivates them, their challenges, and how they navigate both entrepreneurial activities and academic work. Using a snowball approach, a qualitative research design involving fifteen purposively selected respondents from among the sculpture students of the Nsukka Art School was used as a case study. Data collection and analysis were conducted using a semi-structured interview and a thematic analysis approach, respectively. Findings show that respondents are actively involved in entrepreneurial deeds within multiple non-sculpture related fields such as painting, graphic, communication design, T-shirt printing, portrait making, and utility wood sculptures. They are motivated by the quest to address personal financial constraints. Such entrepreneurial quests, however, expose them to specialization and operational, marketing, and managerial challenges. It is recommended that policymakers in academia, industry, and government work together toward repositioning student entrepreneurs by creating the enabling environment for economic growth. While a further study is needed to understand how undergraduates navigate their managerial challenges, the nuanced performance and difference in age and gender is noteworthy.